Innovation and experimentation — landscape in early 16th-century Venetian prints and drawings - Whistler, C (Hirmer Publishers, 2024)
When Marcantonio Michiel (1484-1552) noted the painting by Giovanni Bellini that he had seen in the house of Taddeo Contarini in Venice in 1525 – the St Francis, now in the Frick Collection, New York – his recollection was of a beautiful landscape representing the wilderness that filled the entire picture, into the foreground. In recording another painting on the same visit, Giorgione’s Three Philosophers (Kunsthistorisches Museum, Vienna) Michiel was impressed by the treatment of the imposing craggy outcrop, and the rays of the sun. By the 1520s, Venetian art-lovers were attuned to the delights of such representations, not least because of the innovative exploration of landscape in prints and drawings in the early 1500s that helped to shape a new genre in artistic production. The aspects that caught Michiel’s attention such as the filling of the visual field with natural elements, providing an inviting experience, and the contrasts of wild or rocky stretches with luminous skies, were already characteristic of engravings and independent drawings, notably by Giulio Campagnola (c.1482-post 1517) and by his adoptive son, Domenico Campagnola (c.1500-1564), who were each in their separate ways major protagonists in the development of the Venetian landscape in small-scale monochrome works of art.